Performance, Nutrient Utilization and Organ Characteristics of Broilers Fed Cassava Leaf Meal (Manihot esculenta Crantz) - Iheukwumere, F.C.; Ndubuisi, E.C.; Mazi, E.A.; Onyekwere, M.U. (Pakistan Journal of Nutrition, 2007)
A 35-day feeding trial involving 120, 5-week old Anak broilers was carried out in a completely randomized design to evaluate the performance, nutrient utilization and organ characteristics of broilers fed cassava leaf meal at dietary levels of 0, 5, 10 and 15% respectively. Feed intake, body weight gain, feed conversion ratio and organ weight of birds on the control (0%) and (5%) leaf meals were significantly superior (p<0.05) to the group on 10% and 15% leaf meal. The utilization of Dry Matter (DM), crude protein, ether extract and ash was significantly poorer at the 10 and 15% dietary levels. The organ weights (heart, liver, gizzard) were superior at 0 and 5% (p<0.05) groups to the groups on 10 and 15% inclusion levels of the leaf meal. It is suggested that 5% inclusion of cassava leaf meal could be used in broiler finisher diets without any deleterious effects.